2011
DOI: 10.1103/physreva.84.042329
|View full text |Cite
|
Sign up to set email alerts
|

Quadratic dynamical decoupling: Universality proof and error analysis

Abstract: We prove the universality of the generalized QDD N 1 N 2 (quadratic dynamical decoupling) pulse sequence for near-optimal suppression of general single-qubit decoherence. Earlier work showed numerically that this dynamical decoupling sequence, which consists of an inner Uhrig DD (UDD) and outer UDD sequence using N 1 and N 2 pulses, respectively, can eliminate decoherence to O(T N ) using O(N 2 ) unequally spaced "ideal" (zero-width) pulses, where T is the total evolution time and N = N 1 = N 2 . A proof of th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(56 citation statements)
references
References 53 publications
4
52
0
Order By: Relevance
“…The pioneering strategies for decoupling were introduced in the context of NMR spectroscopy [31]. Since then, many different decoupling sequences have been developed in the context of NMR [32,33,35,36] or QIP [44,46,47,50,53,54,81,97,98].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pioneering strategies for decoupling were introduced in the context of NMR spectroscopy [31]. Since then, many different decoupling sequences have been developed in the context of NMR [32,33,35,36] or QIP [44,46,47,50,53,54,81,97,98].…”
Section: Discussionmentioning
confidence: 99%
“…This reduction comes at the expense of an extension of the cycle time by a factor of four. If the delays between the pulses are allowed to be non-equidistant like in UDD, it becomes possible to create hybrid sequences, such as CUDD [50] and QDD [53,97,98].…”
Section: (C) Dynamical Decoupling Sequences With Multiple Rotation Axesmentioning
confidence: 99%
“…We found that the system-bath interaction term proportional to σ x is suppressed with UDD efficiency for all values of N 1 and N 2 [Eq. (35)]. The interactions proportional to σ z and σ y both exhibit parity effects [Eqs.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a preprint of closely related work by Kuo and Lidar [23] became available, with a different proof of the universality of QDD.…”
Section: Operationmentioning
confidence: 99%